Silicon-doped modified ZnSn (OH) 6 photocatalyst as well as preparation method and application thereof

By doping silicon atoms in ZnSn(OH)6, a silicon-doped modified ZnSn(OH)6 photocatalyst with double anion and cation defect sites was prepared, which solved the problems of low separation efficiency and migration rate of photogenerated carriers and unsatisfactory toluene degradation efficiency in the prior art, and achieved efficient and stable photocatalytic degradation effect.

CN119524832AActive Publication Date: 2025-02-28CHONGQING TECH & BUSINESS UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411708389.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing ZnSn(OH)6 photocatalysts are difficult to achieve efficient photogenerated carrier separation efficiency and migration rate after modification, and are not ideal for the degradation efficiency of the volatile organic toluene, and are prone to produce toxic by-products. The preparation process is complicated, which hinders large-scale application.

Method used

By doping silicon atoms in ZnSn(OH)6 through hydrothermal synthesis, a silicon-doped modified ZnSn(OH)6 photocatalyst with double anion and cation defect sites was prepared. The "crystallization-dissolution-crystallization" mechanism was used to form a catalyst containing flocs covering the cube-shaped structure.

Benefits of technology

It realizes efficient photogenerated carrier separation efficiency and migration rate, significantly improves the photocatalytic degradation activity and stability of toluene, and has broad application prospects for environmental pollution control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524832A_ABST
    Figure CN119524832A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-doped modified ZnSn (OH) 6 photocatalyst as well as a preparation method and application thereof, and belongs to the technical field of photocatalytic materials. The preparation method comprises the following steps: (1) mixing a Zn (Ac) 2.2 H2O solution, a SnCl4. 5H2O solution, a NaOH solution, Na2SiO3. 9H2O, a methylcellulose solution and distilled water to obtain a mixed solution; and (2) heating and synthesizing the mixed solution to obtain the silicon-doped modified ZnSn (OH) 6 photocatalyst. The product is prepared in a hydro-thermal synthesis mode, the method is easy to obtain a material with high crystallinity, the morphology and size of the material can be better controlled, operation is easy, and the prepared silicon-doped modified photocatalyst has the advantages of being stable in activity, high in carrier migration rate and high in separation efficiency, has excellent catalytic performance on toluene volatile organic pollutants, and is suitable for industrial production. The method has a wide application prospect in the field of environmental pollution control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalytic materials, and relates to a silicon-doped modified ZnSn(OH)6 photocatalyst, a preparation method and an application thereof, and specifically relates to a silicon-doped modified ZnSn(OH)6 photocatalyst with double anion and cation defect sites, a preparation method and an application thereof. Background Art

[0002] As a metal hydroxide material with a perovskite crystal structure, ZnSn(OH)6 has a wide band gap (~4eV). Its metal atoms and oxygen atoms present an octahedral coordination structure, forming two polyhedrons, Sn(OH)6 and Zn(OH)6, which form a complete framework by sharing the "O" angle. The surface has abundant hydroxyl groups that can serve as active sites, and under low humidity conditions, it plays a vital role in the generation of surface hydroxyl radicals by hydroxyl radicals. ZnSn(OH)6 itself has a certain number of oxygen vacancies, and a good electronic environment is more conducive to the activation of reactants. The photocatalytic properties of ZnSn(OH)6 can catalyze chemical reactions by absorbing visible light. This means that it can promote the degradation of certain organic matter, the decomposition of water and other reactions under visible light irradiation. With the emphasis on environmental protection and the use of renewable energy, ZnSn(OH)6, as a photocatalyst, may be widely used in water treatment, air purification, photoelectrocatalysis and other fields in the future, providing an effective solution to environmental problems and energy crises.

[0003] However, the modification strategies of morphology control, element doping and heterojunction construction are widely used, but there are many problems, such as expensive modification reagents and no economic benefits; the inevitable introduction of tin oxide and ZnSn(OH)6 to form a heterojunction, while the traditional II-type and Z-type heterojunctions are difficult to effectively separate electron-hole pairs with high redox potentials. The synthetic scheme for its modification is complex, the preparation process is long, and it is difficult to produce on a large scale. The photogenerated carrier separation efficiency and migration rate of the original ZnSn(OH)6 are far from satisfactory. The existing modification strategies and preparation methods are difficult to achieve a ZnSn(OH)6 photocatalyst with fast photogenerated carrier migration rate and stable activity in a short time. In addition, in terms of the removal of volatile organic compound toluene after modification, the degradation efficiency is not ideal, and it is easy to produce toxic byproducts and the preparation process is complicated, which hinders its large-scale application in practice.

[0004] Therefore, how to develop a silicon-doped modified ZnSn(OH)6 photocatalyst with double anion and cation defect sites and its preparation method and application is an urgent problem to be solved by technicians in this field. Summary of the invention

[0005] In view of this, the present invention provides a silicon-doped modified ZnSn(OH)6 photocatalyst and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0008] (1) Zn(Ac)2·2H2O solution, SnCl4·5H2O solution, NaOH solution, Na2SiO3·9H2O, methyl cellulose solution and distilled water are mixed to obtain a mixed solution;

[0009] (2) The mixed solution is heated and synthesized to obtain the above-mentioned silicon-doped modified ZnSn(OH)6 photocatalyst.

[0010] The reaction mechanism of the present invention: The present invention reacts in a hydrothermal synthesis mode according to the "crystallization-dissolution-crystallization" mechanism: Zn 2+ +Sn 4+ +6OH - +Si 4+ →ZnSn(OH)6 (containing Si atoms). The hydrothermal synthesis strategy enables the reactants to react fully and can effectively incorporate silicon atoms into the ZnSn(OH)6 lattice. The silicon-doped modified ZnSn(OH)6 photocatalyst prepared by this method contains only one phase, has double anion and cation defect sites and the ability to produce highly active free radicals, has high efficiency in photogenerated carrier separation, and has high photocatalytic degradation activity and stability for toluene. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is a cubic structure covered with flocs, with a size of 0.3-0.6μm. In the hydrothermal reaction in the reactor, water is used as a medium to help promote the rapid dissolution of SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, and Na2SiO3·9H2O in water, forming a large amount of Sn. 4+ 、Zn 2+ OH - 、Si 4+ ion mixed solution, followed by Zn 2+ +Sn 4+ +6OH - +Si 4+→ZnSn(OH)6 (containing silicon) was synthesized from ZnSn(OH)6 (containing silicon). Methyl cellulose, a surfactant, can effectively collide various ions in the mixture through wetting, dispersing and solubilizing, accelerating the reaction, which helps to provide basic conditions for the efficient preparation of silicon-doped modified ZnSn(OH)6 photocatalysts, so that high-yield and high-activity silicon-doped modified ZnSn(OH)6 catalysts with double anion and cation defect sites can be successfully prepared. The lattice of the silicon-doped modified ZnSn(OH)6 catalyst prepared by adding Na2SiO3·9H2O will be slightly deformed, and the morphology changes from the original cube to a cube surface covered with a layer of flocs.

[0011] The beneficial effects of the present invention are as follows: the present invention adopts a hydrothermal synthesis method to prepare a floc-covered cubic silicon-doped modified ZnSn(OH)6 photocatalyst, which is easy to obtain a material with high crystallinity, can better control the morphology and size of the material, and is easy to operate. The silicon-doped modified ZnSn(OH)6 photocatalyst with double anion and cation defect sites prepared by this method has the characteristics of stable activity, fast carrier migration rate and high separation efficiency, and has excellent catalytic performance for toluene volatile organic pollutants, and has broad application prospects in the field of environmental pollution control.

[0012] Furthermore, the concentration of the above-mentioned Zn(Ac)2·2H2O solution is 0.5mol / L, the concentration of SnCl4·5H2O solution is 0.5mol / L, the concentration of NaOH solution is 3mol / L, the concentration of methylcellulose solution is 2.8g / L, the volume ratio of Zn(Ac)2·2H2O solution, SnCl4·5H2O solution, NaOH solution, methylcellulose solution and distilled water is 4:4:4.6:10:100, and 0.025-1gNa2SiO3·9H2O is added to every 10mL of methylcellulose solution.

[0013] The beneficial effect of adopting the above further technical solution is: the mass of added Na2SiO3·9H2O is selected to be a suitable parameter to avoid the waste of drugs, while effectively ensuring that the silicon-doped modified ZnSn(OH)6 catalyst finally prepared has high catalytic activity for toluene. If the mass ratio of added Na2SiO3·9H2O is too small, the silicon element cannot be incorporated; if the mass ratio of added Na2SiO3·9H2O is too large, the crystallinity of ZnSn(OH)6 will be reduced, the crystal structure will be destroyed, and the activity for toluene will be reduced.

[0014] Furthermore, 0 g, 0.025 g, 0.05 g, 0.75 g, 0.1 g, 0.125 g, 0.25 g, 0.5 g or 1 g Na2SiO3·9H2O was added per 10 mL of methylcellulose solution.

[0015] Furthermore, the solvent of the above-mentioned Zn(Ac)2·2H2O solution, SnCl4·5H2O solution and NaOH solution is water, and the solvent of the methylcellulose solution is water and ethanol, and the mass ratio of water to ethanol is 5:2.

[0016] Furthermore, in step (2), the mixed solution is sealed and heated to 160° C. for 390 minutes.

[0017] The beneficial effect of adopting the above further technical solution is that silicon atoms can be effectively incorporated into the ZnSn(OH)6 lattice at 160°C. Selecting a suitable parameter for the synthesis temperature is convenient for saving synthesis time, while effectively ensuring that the silicon-doped modified ZnSn(OH)6 catalyst finally prepared has high catalytic activity for toluene; if the synthesis temperature is too low, silicon elements cannot be incorporated into ZnSn(OH)6, and silicon atoms cannot effectively replace tin atoms, which easily leads to a decrease in the activity of the generated silicon-doped modified ZnSn(OH)6 catalyst; if the synthesis temperature is too high, not only energy consumption is increased, but also when the temperature exceeds 170°C, Zn2SnO4 will be generated, and the following reactions will occur:

[0018] Zn 2+ +4OH - →Zn(OH)4 2- and ZnSn(OH)6+Zn(OH)4 2- →Zn2SnO4+4H2O+2OH - .

[0019] The temperature was kept at 160℃ for 390min to ensure the full reaction of various elements in the reactor and the yield of silicon-doped modified ZnSn(OH)6 catalyst, which helped to ensure that silicon could be successfully incorporated into the grains of ZnSn(OH)6 catalyst and Sn was successfully introduced. 3+ -OVs double anion defect site; if the insulation stage time is too short, the thermal polymerization reaction of the reactants will be incomplete, the particle size will be uneven, and the silicon element cannot be incorporated; if the insulation stage time is too long, it will lead to the formation of Zn2SnO4.

[0020] Furthermore, in step (2), the mixed solution is sealed and heated for synthesis, the temperature is raised from room temperature to 160° C., and the temperature is kept at 160° C. for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature.

[0021] Furthermore, step (2) also includes: washing the above-mentioned silicon-doped modified ZnSn(OH)6 photocatalyst twice with distilled water and anhydrous ethanol respectively, drying, and grinding to obtain silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0022] The beneficial effect of adopting the above further technical solution is: the silicon-doped modified ZnSn(OH)6 photocatalyst is fully ground into powder to increase the specific surface area, thereby improving the activity of the catalyst in degrading toluene, while facilitating daily detection and use.

[0023] Furthermore, the above-mentioned drying temperature is 60° C. and the drying time is 6 hours.

[0024] Furthermore, the above grinding is performed to a particle size of 0.3-0.6 μm.

[0025] Furthermore, the above preparation method specifically comprises the following steps:

[0026] 1) Divide distilled water into two parts, wherein the volume ratio of the first part of distilled water to the second part of distilled water is 60:40, and mix and stir Zn(Ac)2·2H2O solution, SnCl4·5H2O solution, NaOH solution, Na2SiO3·9H2O and the first part of distilled water to obtain a white solution;

[0027] 2) adding the methylcellulose solution to the white solution and continuing to stir, then adding the second portion of distilled water to mix to obtain a mixed solution;

[0028] 3) The mixed solution is sealed and heated to synthesize, thereby obtaining the above-mentioned silicon-doped modified ZnSn(OH)6 photocatalyst.

[0029] The beneficial effect of adopting the above further technical solution is that in the hydrothermal reaction in the reactor, water is used as a medium and the stirring effect of the rotor is used to promote the rapid dissolution of SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, and Na2SiO3·9H2O in water, forming a large amount of Sn 4+ 、Zn 2+ OH - 、Si 4+ ion mixed solution, followed by Zn 2+ +Sn 4+ +6OH - +Si 4+ →ZnSn(OH)6 (containing silicon element) synthesizes ZnSn(OH)6 (containing silicon element).

[0030] Furthermore, in step 1), the stirring time is 10 min and the stirring speed is 550 r / min; in step 2), the stirring time is 5 min and the stirring speed is 550 r / min.

[0031] The beneficial effect of adopting the above further technical solution is: utilizing the stirring effect of the rotor helps to promote the rapid dissolution of SnCl4·5H2O, Zn(Ac)2·2H2O, NaOH, and Na2SiO3·9H2O in water.

[0032] The present invention also provides a silicon-doped modified ZnSn(OH)6 photocatalyst prepared by the above method.

[0033] The present invention also provides an application of the silicon-doped modified ZnSn(OH)6 photocatalyst in removing toluene pollutants.

[0034] The beneficial effect of the present invention is that compared with conventional unmodified ZnSn(OH)6, the silicon-doped modified ZnSn(OH)6 catalyst with double anion and cation defect sites prepared by the present invention has significantly higher photocatalytic (ultraviolet light) toluene activity than unmodified ZnSn(OH)6. Therefore, the silicon-doped modified ZnSn(OH)6 photocatalyst with double anion and cation defect sites of the present invention can be used in removing toluene pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The photocatalytic toluene removal activity test diagram of the products obtained in Comparative Example 1 and Examples 1-8 under ultraviolet light irradiation; in the figure, the vertical axis value represents the toluene removal activity percentage, and the removal rate is the difference before and after photocatalysis (the same below);

[0036] Figure 2 This is a comparison chart of the photocatalytic removal of toluene by the products obtained in Example 8, Comparative Example 2 and Comparative Example 3 under ultraviolet light irradiation;

[0037] Figure 3 It is a dot-line graph of the photocatalytic toluene removal activity test of the product obtained in Comparative Example 1 under different humidity concentrations of air;

[0038] Figure 4 It is a dot-line graph of the photocatalytic toluene removal activity test of the product obtained in Example 8 under different humidity concentrations of air;

[0039] Figure 5 It is a dot-line graph of the activity stability test of photocatalytic removal of toluene pollutants in Example 8 within 335 minutes;

[0040] Figure 6 X-ray diffraction spectra of cubic silicon-doped modified ZnSn(OH)6 prepared in Comparative Example 1 and Examples 1-8;

[0041] Figure 7 is a scanning electron microscope image of the product obtained in Example 8;

[0042] Figure 8 The XPS full spectra of Comparative Example 1 and Example 8 are shown;

[0043] Fig. 9 XPS high-resolution O1s spectra of Comparative Example 1 and Example 8;

[0044] Fig.10 The photocurrent diagram of the products obtained in Comparative Example 1 and Example 8;

[0045] Fig.11 The electrochemical impedance diagrams of the products obtained in Comparative Example 1 and Example 8 are shown;

[0046] Fig.12 The electron paramagnetic resonance images of the products obtained in Comparative Example 1 and Example 8 are shown. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The solvents of the methyl cellulose solution in the examples and comparative examples of the present application are water and ethanol, and the mass ratio of water to ethanol is 5:2.

[0049] Example 1

[0050] The preparation method of silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0051] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution, 4.6 mL of 3 mol / L NaOH aqueous solution and 0.025 g of Na2SiO3·9H2O were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0052] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0053] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, and the temperature is raised from room temperature to 160°C, and kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is ground to a particle size of 0.3-0.6μm to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0054] Example 2

[0055] The preparation method of silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0056] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution, 4.6 mL of 3 mol / L NaOH aqueous solution and 0.05 g of Na2SiO3·9H2O were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0057] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0058] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, and the temperature is raised from room temperature to 160°C, and kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is ground to a particle size of 0.3-0.6μm to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0059] Example 3

[0060] The preparation method of silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0061] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution, 4.6 mL of 3 mol / L NaOH aqueous solution and 0.075 g of Na2SiO3·9H2O were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0062] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0063] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, and the temperature is raised from room temperature to 160°C, and kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is ground to a particle size of 0.3-0.6μm to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0064] Example 4

[0065] The preparation method of silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0066] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution, 4.6 mL of 3 mol / L NaOH aqueous solution and 0.1 g of Na2SiO3·9H2O were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0067] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0068] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, and the temperature is raised from room temperature to 160°C, and kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is ground to a particle size of 0.3-0.6μm to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0069] Example 5

[0070] The preparation method of silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0071] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution, 4.6 mL of 3 mol / L NaOH aqueous solution and 0.125 g of Na2SiO3·9H2O were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0072] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0073] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, and the temperature is raised from room temperature to 160°C, and kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is ground to a particle size of 0.3-0.6μm to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0074] Example 6

[0075] The preparation method of silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0076] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution, 4.6 mL of 3 mol / L NaOH aqueous solution and 0.5 g of Na2SiO3·9H2O were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0077] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0078] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, and the temperature is raised from room temperature to 160°C, and kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is ground to a particle size of 0.3-0.6μm to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0079] Example 7

[0080] The preparation method of silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0081] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution, 4.6 mL of 3 mol / L NaOH aqueous solution and 1 g of Na2SiO3·9H2O were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0082] (2) Add 10 mL of 2.8 g / L methylcellulose solution to the white solution and continue stirring for 5 min at a stirring speed of 550 r / min, then add 40 mL of distilled water to mix and obtain a mixed solution;

[0083] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, and the temperature is raised from room temperature to 160°C, and kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is ground to a particle size of 0.3-0.6μm to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0084] Example 8

[0085] The preparation method of silicon-doped modified ZnSn(OH)6 photocatalyst comprises the following steps:

[0086] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution, 4.6 mL of 3 mol / L NaOH aqueous solution and 0.25 g of Na2SiO3·9H2O were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0087] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0088] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, and the temperature is raised from room temperature to 160°C, and kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst. The obtained silicon-doped modified ZnSn(OH)6 photocatalyst is ground to a particle size of 0.3-0.6μm to obtain a silicon-doped modified ZnSn(OH)6 photocatalyst powder.

[0089] Comparative Example 1

[0090] The preparation method of ZnSn(OH)6 photocatalyst comprises the following steps:

[0091] (1) 4 mL of 0.5 mol / L Zn(Ac)2·2H2O aqueous solution, 4 mL of 0.5 mol / L SnCl4·5H2O aqueous solution and 4.6 mL of 3 mol / L NaOH aqueous solution were added to 60 mL of distilled water and mixed and stirred for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0092] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0093] (3) The mixed solution was transferred into a stainless steel autoclave lined with Teflon. After the autoclave was sealed, it was placed in an oven for heating and synthesis. The temperature was raised from room temperature to 160°C and kept at 160°C for 390 min. After the synthesis was completed, the heating temperature was lowered to room temperature. The obtained precipitate was washed twice with distilled water and anhydrous ethanol, respectively, and dried at 60°C for 6 h to obtain a ZnSn(OH)6 photocatalyst. The obtained ZnSn(OH)6 photocatalyst was ground to a particle size of 0.3-0.6 μm to obtain a ZnSn(OH)6 photocatalyst powder.

[0094] Comparative Example 2

[0095] The preparation method of silicon-doped modified CaCO3 photocatalyst comprises the following steps:

[0096] (1) Add 5 g of CaCO3 (5 g is the amount of synthesized ZnSn(OH)6 sample) and 0.25 g of Na2SiO3·9H2O into 60 mL of distilled water and stir for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0097] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0098] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, the temperature is raised from room temperature to 160°C, and the temperature is kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified CaCO3 photocatalyst. The obtained silicon-doped modified CaCO3 photocatalyst is ground to a particle size of 0.3-0.6 μm to obtain a silicon-doped modified CaCO3 photocatalyst powder.

[0099] Comparative Example 3

[0100] The preparation method of silicon-doped modified TiO2 photocatalyst comprises the following steps:

[0101] (1) Add 5 g TiO2 (5 g is the amount of synthesized ZnSn(OH)6 sample) and 0.25 g Na2SiO3·9H2O into 60 mL distilled water and stir for 10 min at a stirring speed of 550 r / min to obtain a white solution;

[0102] (2) adding 10 mL of 2.8 g / L methyl cellulose solution to the white solution and continuing stirring for 5 min at a stirring speed of 550 r / min, adding 40 mL of distilled water to mix and obtain a mixed solution;

[0103] (3) The mixed solution is transferred into a stainless steel autoclave lined with Teflon. After the autoclave is sealed, it is placed in an oven for heating synthesis, the temperature is raised from room temperature to 160°C, and the temperature is kept at 160°C for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature, and the obtained precipitate is washed twice with distilled water and anhydrous ethanol, and dried at 60°C for 6 hours to obtain a silicon-doped modified TiO2 photocatalyst. The obtained silicon-doped modified TiO2 photocatalyst is ground to a particle size of 0.3-0.6 μm to obtain a silicon-doped modified TiO2 photocatalyst powder.

[0104] Performance characterization experiments of different photocatalysts

[0105] A number of characterization experiments were carried out using the photocatalysts of Examples 1-8 and Comparative Examples 1-3, wherein the photocatalysts of Examples 1 to 8 can be abbreviated as ZHS-5, ZHS-10, ZHS-15, ZHS-20, ZHS-25, ZHS-100, ZHS-200, and ZHS-50 in the experimental results, respectively, and the photocatalysts of Comparative Example 1, Comparative Example 2, and Comparative Example 3 can be abbreviated as ZHS, Si-Ca, and Si-Ti, respectively, in the experimental results.

[0106] 1. Photocatalytic activity characterization experiment

[0107] Experimental methods:

[0108] The performance of the catalyst was evaluated by real-time monitoring of the instantaneous concentration of ppm-level VOCs in the reaction chamber using a photoacoustic spectrometer at room temperature. The specific operation is as follows: 4 samples of 0.1g were weighed on 40mm×100mm rectangular rounded frosted glass sheets, evenly dispersed with a small amount of alcohol, and dried in a constant temperature drying oven at 60°C. After cooling to room temperature, the glass sheet loaded with the catalyst was placed in a rectangular continuous flow reaction chamber with a volume of 0.34L (i.e., 200mm×100mm×17mm), and a layer of quartz glass was placed on the reaction chamber to seal the reaction chamber (fixed with screws to prevent air leakage). At the same time, a 300W commercial mercury lamp was used above the reaction chamber as the ultraviolet light source for the photocatalytic reaction; the initial concentration of the pollutant was changed by adjusting the flowmeter on the gas path, and the flow rate of the humid air was set to 0.5L·min -1 , dry air flow rate (0.4L·min -1 ) and the flow rate of pollutants (0.1L·min -1 ) is 0.5L·min -1 , the diluted VOCs pollutant gas is introduced into the reaction chamber. Under dark conditions, after the catalyst reaches the adsorption-desorption equilibrium, the light is turned on to carry out the pollutant degradation reaction, and the toluene concentration in the reaction chamber is recorded using a photoacoustic spectrometer.

[0109] Figure 1-Figure 5The photocatalytic toluene activity diagram of the experimental process is shown in Figure 2. Figure 2 As shown, the photocatalytic oxidation activity of 50ppm toluene prepared by Example 8, Comparative Examples 2 and Comparative Examples 3 was 100%, deactivated, decreased in activity and then deactivated. This shows that among some wide bandgap semiconductors, only ZnSn(OH)6 has better toluene degradation performance after being doped with silicon, CaCO3 is inactive, and TiO2 is very unstable. Moreover, from Figure 1 It can be seen that the photocatalytic activity of ZnSn(OH)6 photocatalyst (Examples 1-6) for 50ppm toluene oxidation is higher than 80%, and in Example 8, Examples 2-5, the toluene oxidation activity is 100%;

[0110] like Figure 3 As shown, the photocatalytic oxidation activity of 50 ppm toluene in Comparative Example 1 at different humid air concentrations (0%, 25%, 50%, 75%, 100%, the same below) is about 70%; Figure 4 As shown, the photocatalytic oxidation activity of 50 ppm toluene in Example 8 at different humid air concentrations is greater than 70%, and the activity can reach 100% at 50% humid air.

[0111] In addition, the present invention conducted a stability test on Example 8 ( Figure 5 ), and found that its photoactivity towards toluene did not decrease within 335 min, and the degradation rate was maintained at 100%, indicating that the photocatalytic performance of ZnSn(OH)6 catalyst after silicon was incorporated into the catalyst by hydrothermal method was excellent, stable and efficient.

[0112] 2. XRD characterization experiment

[0113] In order to verify the types of the products obtained in Comparative Example 1 and Examples 1-8, the present invention uses a German Bruker D8Advance X-ray diffractometer (Cu Kα, λ=0.154 nm, working voltage and working current are 40 kV and 40 mA respectively) to perform XRD tests on each product.

[0114] like Figure 6As shown, the XRD results show that the diffraction peaks of the products obtained in Example Comparative Example 1, Examples 1-5, Examples 8, and Examples 6-7 at 19.69°, 22.78°, 32.44°, 40.04°, 46.64°, 52.42°, and 57.72° correspond to the ZnSn(OH)6 (JCPDS 74-1825) (111), (200), (220), (222), (400), (420), and (422) planes, respectively, and no other impurity peaks are found. However, as the doping amount increases, the ZHS-x peak intensity gradually decreases. This indicates that the addition of excessive sodium silicate will reduce the crystallinity of the material. In addition, all the diffraction peaks have slightly shifted toward high diffraction angles. This may be because the introduction of sodium silicate changes the coordination environment of the crystal, resulting in deformation of the lattice.

[0115] 3. Electron microscopy characterization experiment

[0116] The present invention uses a Japanese JEOL Model JSM-6490 scanning electron microscope to characterize the sample morphology of Example 8. Figure 7 As shown, it can be found that the size of silicon-doped modified ZnSn(OH)6 with flocculent-covered cubic morphology is between 0.3-0.6 μm.

[0117] 4. XPS characterization experiment

[0118] like Figure 8 As shown in the XPS full spectrum comparison diagram of Example 8 and Comparative Example 1, in Example 8, 101.9 eV is assigned to Si 2p, confirming that silicon has been incorporated into ZnSn(OH)6. Fig. 9 As shown, the peak at 531.5 eV in Example 8 is assigned to defective oxygen, accounting for 70.57%, which is significantly higher than the defective oxygen peak in Comparative Example 1. This indicates that silicon doping introduces more oxygen vacancies, which is beneficial to the activation of small molecules.

[0119] 5. Electrochemical characterization experiments

[0120] like Fig.10 As shown in the figure, the photocurrent of Example 8 is compared with that of Comparative Example 1. In 1400s, the photocurrent of Example 8 is higher than that of Comparative Example 1, which proves that Example 8 is more likely to promote the generation of electrons and improve the separation efficiency of electron-hole pairs. Fig.11 As shown, the electrical impedance of Example 8 is less than that of Comparative Example 1, which proves that Example 8 accelerates the migration rate of carriers.

[0121] 6. Electron Paramagnetic Resonance

[0122] Oxygen vacancies and Sn in the crystal structure 3+ The sites usually act as defects that trap electrons and holes, making them paramagnetic centers. Fig.12 As shown, by observing the electron paramagnetic resonance, it is found that Example 8 has a symmetrical peak at 1.96, which is due to the captured photogenerated electrons (i.e. Sn 3+ ). Theoretically, oxygen vacancies and Sn 3+ The sites should coexist in Example 8, but no signal belonging to oxygen vacancies was detected. This may be because the oxygen vacancies on the surface are not stable yet. The defect sites are mainly Sn 3+ For Comparative Example 1, no signal of electron capture was observed, which indicates that the introduction of silicon can induce Sn 3+ The occurrence of defects.

[0123] The disclosed embodiments are described to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst, characterized in that: The following steps are involved: (1) Zn(Ac)2·2H2O solution, SnCl4·5H2O solution, NaOH solution, Na2SiO3·9H2O, methyl cellulose solution and distilled water are mixed to obtain a mixed solution; (2) The mixed solution is heated and synthesized to obtain the silicon-doped modified ZnSn(OH)6 photocatalyst.

2. The method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst according to claim 1, characterized in that: The concentration of the Zn(Ac)2·2H2O solution is 0.5 mol / L, the concentration of the SnCl4·5H2O solution is 0.5 mol / L, the concentration of the NaOH solution is 3 mol / L, the concentration of the methyl cellulose solution is 2.8 g / L, the volume ratio of the Zn(Ac)2·2H2O solution, the SnCl4·5H2O solution, the NaOH solution, the methyl cellulose solution and distilled water is 4:4:4.6:10:100, and 0.025-1 g Na2SiO3·9H2O is added to every 10 mL of the methyl cellulose solution.

3. The method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst according to claim 1, characterized in that: In step (2), the mixed solution is heated to 160° C. and kept warm for 390 min.

4. The method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst according to claim 1, characterized in that: In step (2), the mixed solution is heated for synthesis, the temperature is raised from room temperature to 160° C., and the temperature is kept at 160° C. for 390 minutes. After the synthesis is completed, the heating temperature is lowered to room temperature.

5. The method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst according to claim 1, characterized in that: Step (2) also includes: washing the silicon-doped modified ZnSn(OH)6 photocatalyst twice with distilled water and anhydrous ethanol respectively, drying, and grinding to obtain silicon-doped modified ZnSn(OH)6 photocatalyst powder.

6. The method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst according to claim 5, characterized in that: The drying temperature is 60° C. and the drying time is 6 hours.

7. The method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst according to claim 5, characterized in that: The grinding process is performed to a particle size of 0.3-0.6 μm.

8. The method for preparing a silicon-doped modified ZnSn(OH)6 photocatalyst according to claim 1, characterized in that: The specific steps include: 1) Divide distilled water into two parts, wherein the volume ratio of the first part of distilled water to the second part of distilled water is 60:40, and mix and stir Zn(Ac)2·2H2O solution, SnCl4·5H2O solution, NaOH solution, Na2SiO3·9H2O and the first part of distilled water to obtain a white solution; 2) adding the methylcellulose solution to the white solution and continuing to stir, then adding the second portion of distilled water to mix to obtain a mixed solution; 3) The mixed solution is sealed and heated for synthesis to obtain the silicon-doped modified ZnSn(OH)6 photocatalyst.

9. A silicon-doped modified ZnSn(OH)6 photocatalyst prepared by the method according to any one of claims 1 to 8.

10. Use of the silicon-doped modified ZnSn(OH)6 photocatalyst according to claim 9 in removing toluene pollutants.

Citation Information

Patent Citations

  • Preparation method and application of zinc hydroxystannate photocatalyst

    CN116393118A

  • Composite photocatalyst as well as preparation method and application thereof

    CN116393119A

  • Zinc hydroxystannate cubic photocatalyst as well as preparation method and application thereof

    CN116851005A